Business Strategy for Sustainable Growth of a Consultant IT Company (Case Study of PT. Mulya, Jakarta, Indonesia) - Mulya, Haekal Hanifah; Rahadi, Raden Aswin; Siahaan, Uke Marius (Jurnal Indonesia Sosial Sains, 2025)
Technology is a key driver of sustainable business practices in the modern digital era, significantly improving operational efficiency and supporting sustainable consumption. The digital transformation of activities such as shopping and information exchange has accelerated technological development globally, including in Indonesia. Government initiatives, such as expanding internet networks, implementing digital payment systems, digitizing population data, and creating smart cities, have provided ample opportunities for the technology sector, including IT consulting firms like PT. Mulya in Jakarta. This research aims to identify the most sustainable and profitable strategic option for PT. Mulya to ensure its long-term growth and resilience amidst growing investor interest. The study adopts both qualitative and quantitative approaches, focusing on financial aspects relevant to sustainable business practices. The analysis includes a financial position audit, company valuation, and financial projections for PT. Mulya. The results offer insights into PT. Mulya's financial standing, providing clarity on the most viable strategic option among four proposed: majority acquisition, minority acquisition, joint cooperation, or rejecting the offer. The findings indicate the potential for PT. Mulya to enhance profitability and ensure sustainability with the right strategy. PT. Mulya can optimize its growth and sustainability by adopting the most suitable strategic option based on the research's findings. The study emphasizes the importance of aligning strategy with long-term financial goals for sustainable success. The study's implications provide valuable guidance for PT. Mulya and other similar firms in making informed strategic decisions that balance profitability with sustainability in a rapidly evolving digital landscape.